Analisis Bahan Ajar Keragaman Suku Bangsa dan Budaya dalam Implementasi Karakter Toleransi di Sekolah Dasar - Sari, Mia Zultrianti; Fitriyani, Yani; Amalia, Dwi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study aims to know the extent the character of tolerance is embedded in the students. Through this social science subject, students can learn about the study of cultural diversity, the environment and community life which can be used as a forum for implementing tolerance characters in everyday life. This research method used a survey with a qualitative descriptive approach. The research was conducted in all Elementary Schools of Losari District, Brebes Regency. The research data were obtained from the results of filling out a questionnaire for grade IV teachers and students. The data analysis technique used was with the help of Microsoft Excel. The results of the analysis of teaching materials on ethnic and cultural diversity showed that 75% relevance was said to be in the good relevant category. The results of the research of all elementary school class teachers in Losari District on the implementation of the character of tolerance in the social science subject showed a relevance of 53.33% including the very good category. Then the results of the research of class IV students on the development of the character of tolerance in social science subjects showed a relevance of 66.67% which was categorized quite good. These results show that through the analysis of teaching materials for the diversity of ethnic groups and cultures in Elementary Schools of Losari District, it can be concluded that the character of tolerance in students of Elementary Schools has been implemented.